Transformations in slavery : a history of slavery in Africa - Lovejoy, Paul E. (Cambridge ; New York : Cambridge University Press, 2011)
"This history of African slavery from the fifteenth to the early twe ntieth centuries examines how indigenous African slavery developed with in an international context. The new edition revises statistical materi al and incorporates recent research"--
Machine generated contents note: 1. Africa and slavery; 2. On the fr ontiers of Islam, 1400-1600; 3. The export trade in slaves, 1600-1800; 4. The enslavement of Africans, 1600-1800; 5. The organization of slave marketing, 1600-1800; 6. Relationships of dependency, 1600-1800; 7. Th e nineteenth-century slave trade; 8. Slavery and 'legitimate trade' on the west African coast; 9. Slavery in the savanna during the era of the Jihads; 10. Slavery in central, southern, and eastern Africa in the ni neteenth century; 11. The abolitionist impulse; 12. Slavery in the poli tical economy of Africa.
Includes bibliographical references (p. 355-363) and index.
Keywords: Slavery -- Africa -- History; Slave trade